Estudo de sistemas microemulsionados utilizando água do mar na recuperação avançada de petróleo - Paulino, Luísa Cimatti (2007)
Petroleum exists in the nature in certain underground formations where it is adsorbed into the rocks pores. For the conventional recovery methods usually only 30% of the oil is extracted and this can be credited, basically, to three aspects: high viscosity of the oil, geology of the formation and high interfacial tensions between the reservoir s fluids. The enhanced recovery methods use the injection of a fluid or fluids mixture in a reservoir to act in points where the conventional process didn't reach the recovery rates. Microemulsion flooding, considered an enhanced method, has the purpose to desorb the oil from the rock formation and to attain an efficient displacement of the oil emulsion. With this in mind, this work was accomplished with two main objectives: the study of the parameters effect that influence a microemulsified system (surfactant and cosurfactant types, C/S rate and salinity) and the evaluation of displacement efficiency with the microemulsions that showed stability in the rich aqueous area. For the analyzed parameters it was chose the microemulsions composition used in the recovery stage: 25% water, 5% kerosene, 46.7% of butanol as cosurfactant and 23.3% of BC or SCO cosurfactant. The core plugs of Assu and Botucatu sandstones were appraised in porosity and permeability tests and then submitted to the steps of saturation with seawater and oil, conventional recovery with water and enhanced recovery with the selected microemulsions. The Botucatu sandstone presented better recovery parameters, and the microemulsion composed with BS surfactant had larger recovery efficiency (26.88%)